The effect of auricular vagus nerve stimulation on electroencephalography and electromyography measurements in healthy persons - Konakoğlu, Gülşah; Özden, Ali Veysel; Solmaz, Hakan; Bildik, Celaleddin (Frontiers in Physiology, 2023)
Objectives: Auricular vagus nerve stimulation (VNS) is a non-invasive treatment modality. Opinions that it can be used in the treatment of various clinical problems have gained importance in recent years. In this study, it was aimed to lay the groundwork for the use of the auricular VNS in different ears. Methods: Healthy individuals (n = 90) were divided into three groups: unilateral left (n = 30), unilateral right (n = 30), and bilateral (n = 30) auricular VNS. Electroencephalography (EEG) and electromyography (EMG) measurements were performed before and after auricular VNS (10 Hz, 300 µs, 20 min) for a single session. Results: An increase in wrist extensor muscles activation was detected on the contralateral side of the auricular VNS application side. It has been observed that there is a general decrease in the power of high-frequency waves and an increase in the power of lower-medium frequency waves in various parts of the brain. Conclusion: Our findings suggest that the projection of the auricular VNS in the central nervous system may also affect the corticospinal tracts.